Дошкільна освіта в дискурсі філософських рефлексій - Іванова, Н. В.; Ivanova, N. V. (Східноєвропейський національний університет імені Лесі Українки, 2013)
Розкрито філософсько-освітні аспекти сучасного освітнього простору дошкілля, проблеми світоглядної цілісності та цінності знань у контексті актуалізації філософського мислення. The article deals with the problems of modern pre-school education in the context of transformational changes in the society. The main approaches to the question of the outlook integrity of educational paradigm of the pre-school bringing up and about the child’s integration into the society and mastering personal value-semantic universum are observed in the article. Pre-school child, his life in existentional values of spirit is the object of modern philosophical-educational reflections. The question about the quantity, quality and content of knowledge, its ethic and health-protection direction, ecological security in the context of building the society of knowledge is revealed here. The necessity of scientific elaboration and instillation of the educational course «Philosophy for pre-school children» into the practice of pre-school education is grounded in the article.
Pre-school Education in the Discourse of Philosophical Reflections
Keywords: дошкільна освіта; pre-school education; освітня парадигма; educational paradigm; світогляд; outlook; цінності; values; знання; knowledge; філософське мислення; philosophical thinking